1978
DOI: 10.1039/f29787402246
|View full text |Cite
|
Sign up to set email alerts
|

Triplet excited states of carbonyl-containing polyenes

Abstract: The techniques of pulse radiolysis, laser flash photolysis and conventional flash photolysis have been used to study several properties of the lowest triplet states of a series of related carbonyl polyenes : ,!3-ionone, /3-ionylidene acetaldehyde, /3-apo-l4'-carotenal, P-ap0-8'-carotenal and torularhodinaldehyde. The corresponding triplet-triplet (T-T) absorption spectra, triplet lifetimes, triplet extinctions, quantum efficiencies of production of the lowest triplet for 265 nm excitation and lowest triplet en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2
2

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 1 publication
5
17
2
2
Order By: Relevance
“…Figure 2 shows the transient absorption spectrum of the triplet state of β‐ionone ( 3 1* ) obtained by laser‐flash photolysis upon excitation at 355 nm of 3 m m 1 in argon‐saturated toluene solution. The transient absorption maximum at 335 nm and lifetime of 132 ns for 3 1* were similar to those reported in hexane (23) and benzene (24). The triplet quantum yield ( Φ T ) of 3 1* was determined by time‐resolved photoacoustic experiments Figure 3.…”
Section: Resultssupporting
confidence: 82%
“…Figure 2 shows the transient absorption spectrum of the triplet state of β‐ionone ( 3 1* ) obtained by laser‐flash photolysis upon excitation at 355 nm of 3 m m 1 in argon‐saturated toluene solution. The transient absorption maximum at 335 nm and lifetime of 132 ns for 3 1* were similar to those reported in hexane (23) and benzene (24). The triplet quantum yield ( Φ T ) of 3 1* was determined by time‐resolved photoacoustic experiments Figure 3.…”
Section: Resultssupporting
confidence: 82%
“…50 However, for intermolecular triplet-triplet energy transfer for ployenes with a series of donors varying at triplet energy level, the observed tendency of quenching efficiency is opposite to what is expected from the energy gap law. 46 Our observation suggests that the triplet energy transfer occurring at the interface is more like an internal conversion process; this may reflect the unique properties of interfacially bounded molecules, and such a discrepancy remains for further investigation.…”
Section: ) Triplet Absorption Spectrum Of the Ester-like Linkage Modmentioning
confidence: 80%
“…The reported triplet energy level for 8-apo-8′-carotenal is 1.27 eV above the ground state, which is close to that of the chelating form. 46 When 8-apo-8′-carotenal was used as a triplet energy quencher, we found that the triplet absorption signal of surface species can be selectively quenched with varied efficiency, i.e., the triplet state of the chelating and bridging form is more vulnerable to the carotenal quenching. Figure 8 displays the time-resolved transient absorbance difference spectra of ATRA/TiO 2 in ethanol delayed at 10 µs at varied concentrations of the quencher.…”
Section: ) Triplet Absorption Spectrum Of the Ester-like Linkage Modmentioning
confidence: 98%
“…Uma exceção a esta regra geral é feita no caso particular de alguns carotenóides de pequena cadeia conjugada como β-ionona, retinal e β-apo-14'-carotenal, onde a formação do estado triplete por excitação direta pode ser observada, sendo tal fato atribuído a existência de um estado 3 ππ próximo ou abaixo do estado singlete de mais baixa energia 1 nπ para β-ionona e retinal e, a um estado 3 nπ abaixo do estado singlete de natureza 1 ππ no caso de β-apo-14'-carotenal 36 . Tipicamente o estado triplete de um carotenóide pode ser populado via processos de transferência de energia utilizando-se um sensibilizador apropriado.…”
Section: O Estado Triplete De Carotenóidesunclassified
“…Este transiente pode ser observado através de técnicas como fotólise de pulso e radiólise de pulso, apresentando esta última a vantagem de poder ser usada para excitar diretamente o estado triplete através de um mecanismo de recombinação de íons e , portanto não envolvento o processo de cruzamento intersistemas 37 . Em geral, as mesmas tendências observadas acima para os espectros de absorção do estado fundamental podem ser extendidas para os espectros de absorção do estado triplete, isto é, aumento do coeficiente de absorção molar e deslocamento para o vermelho do λ max em função do aumento do número de ligações duplas conjugadas do carotenóide 17,36 . Devido ao fato de carotenóides serem não fosforescentes, os métodos mais empregados para a determinação da energia deste estado têm sido: transferência de energia [36][37][38][39][40][41][42][43] , acoplamento spin-órbita 44 e, recentemente espectroscopia de fotoacústica pulsada, utilizando também sensibilizadores para gerar o estado triplete dos carotenóides 45 .…”
Section: O Estado Triplete De Carotenóidesunclassified